NK Cell IL-10 Production Requires IL-15 and IL-10 Driven STAT3 Activation - Clark, Sarah E.; Burrack, Kristina S.; Jameson, Stephen C.; Hamilton, Sara E.; Lenz, Laurel L. (Frontiers in Immunology, 2019)
Natural killer (NK) cells can produce IFNγ or IL-10 to regulate inflammation and immune responses but the factors driving NK cell IL-10 secretion are poorly-defined. Here, we identified NK cell-intrinsic STAT3 activation as vital for IL-10 production during both systemic Listeria monocytogenes (Lm) infection and following IL-15 cytokine/receptor complex (IL15C) treatment for experimental cerebral malaria (ECM). In both contexts, conditional Stat3 deficiency in NK cells abrogated production of IL-10. Initial NK cell STAT3 phosphorylation was driven by IL-15. During Lm infection, this required capture or presentation of IL-15 by NK cell IL-15Rα. Persistent STAT3 activation was required to drive measurable IL-10 secretion and required NK cell expression of IL-10Rα. Survival-promoting effects of IL-15C treatment in ECM were dependent on NK cell Stat3 while NK cell-intrinsic deficiency for Stat3, Il15ra, or Il10ra abrogated NK cell IL-10 production and increased resistance against Lm. NK cell Stat3 deficiency did not impact production of IFNγ, indicating the STAT3 activation initiated by IL-15 and amplified by IL-10 selectively drives the production of anti-inflammatory IL-10 by responding NK cells.